2018
DOI: 10.21608/edj.2018.78529
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Treatment For Temporomandibular Joint Internal Derangement: A Randomized controlled clinical study

Abstract: Background: Temporomandibular joint (TMJ) disorders are among the common causes of facial pain. Internal derangement is the most common intra-articular TMJ disorder.Objective: The aim of this study was to evaluate the efficacy of ozone application in arthrocentesis of temporomandibular joints with internal derangement. Patients and methods:Thirty patients were recruited in this study. They presented with limited function and pain related to the TMJ. They were randomly and equally divided in two groups; group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, group A reported better improvement in the mouth opening at T1 and T4. The ozonized water had a positive impact on such findings and this was in accordance with Elsholkamy, 14 2018 in his study, he stated that mouth opening improved significantly for all patients treated with ozonized water as the mean increased from 28 mm preoperatively to 41 mm postoperatively. The present study scored no significant association between sex and mouth opening, which is parallel with another study performed by Grossmann et al, 15 2019, who illustrated no association between the results of sex and mouth opening (P > 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…However, group A reported better improvement in the mouth opening at T1 and T4. The ozonized water had a positive impact on such findings and this was in accordance with Elsholkamy, 14 2018 in his study, he stated that mouth opening improved significantly for all patients treated with ozonized water as the mean increased from 28 mm preoperatively to 41 mm postoperatively. The present study scored no significant association between sex and mouth opening, which is parallel with another study performed by Grossmann et al, 15 2019, who illustrated no association between the results of sex and mouth opening (P > 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…Finally, Yamaner et al 17 reported no significant differences between treatments. On the other hand, concerning arthrocentesis with ozone, another three studies 20 21 22 reported an improvement in MMO in TMD treated with OT.…”
Section: R Esultsmentioning
confidence: 98%
“…Then, 10 full-text articles were retrieved, 2 of which were excluded with reasons. Eight articles 16 17 18 19 20 21 22 23 reported the use of OT for the treatment of TMD and the data extracted from these studies are listed in Additional Table 1 . No gray literature matched the eligibility criteria.…”
Section: R Esultsmentioning
confidence: 99%
See 2 more Smart Citations